Relationship quality determinants and outcomes in retail banking services: The role of customer experience - Teresa Fernandes (2019)
Cultivating high quality relationships with customers is of paramount importance in the banking sector. However, there has been little effort to examine relationship quality (RQ) in financial services, and though the evaluation of RQ should depend on the experience provided, empirical evidence on how customer experience may contribute to RQ is scant. Therefore, based on data collected from 227 retail banking clients, analysed using PLS-SEM, the purpose of this study is to understand the role played by customer experience on RQ in retail banking, and its impact on relational outcomes, comparing customers with and without a dedicated account manager.